Integration of STEAM Approach in Mathematics Learning to Enhance Creativity of Elementary School Students - Febriarsita Eka Sasmita; Nunik Hidayati; Prafita Fardhany Aslam (Journal of Innovative and Creativity, 2025)
Creativity constitutes a fundamental competency for meeting the complex demands of the 21st century and should be cultivated from an early age, particularly within the context of mathematics education. This study aims to analyze the integration of the STEAM approach in mathematics learning as an effort to enhance the creativity of elementary school students. The study was conducted using a descriptive qualitative method through a literature review by analyzing eight relevant national and international articles related to the research topic. The results indicate that the STEAM approach is effective in developing three creativity indicators: fluency (the ability to generate many ideas), flexibility (the ability to think from various perspectives), and novelty (originality in ideas and solutions). Students become more active, able to solve problems innovatively, and relate mathematical concepts to real-life situations through project-based activities. The implementation of the STEAM approach also faces several challenges, including limited time, facilities and infrastructure, and teacher readiness. Therefore, continuous efforts are needed to optimize the integration of the STEAM approach to produce creative, adaptive students who are ready to face future challenges.